Basari, Syifa Fadhila The Relationship Between Housing Density and Family Resilience In Urban Densely Populated Areas In Kampung Rawa Urban Village, Central Jakarta Administrative City - Fadhila Basari, Syifa; Hasanah, Uswatun; Kabbaro, Hurriyyatun (Journal of Geography Science and Education, 2024)
Families who live in densely populated settlements or in areas that are vulnerable to various problems, including economic, educational, health and other social problems, are unable to carry out their roles and functions properly. People in Kampung Rawa often depend on government assistance to fulfill their basic needs to maintain their economic resilience, which is also related to their social and psychological resilience. This tends to create dependency that inhibits individual and family initiatives to be independent. This study aims to determine the relationship between housing density and family resilience in densely populated urban areas. This research is a quantitative study using a survey method, with a correlation approach. Data collection in this study used a questionnaire. Data collection used cluster sampling technique with 476 housewives in RW 2, Kampung Rawa Village, Central Jakarta. Research data collection from March 2024 to September 2024. The prerequisite test data analysis technique uses the Kolmogorov-Smirnov normality test and hypothesis testing using the Person Product Moment Correlation Coefficient Test and the t test. The results showed that the value of r = 0.007 means that it has a very weak relationship or H0 is accepted. This means that there is no relationship between residential density and family resilience in urban densely populated areas in the kampung rawa urban village of Central Jakarta. The implication of this research is that by paying attention to residential capacity, families can create a more comfortable and healthy environment. Families who prioritize wise family planning can minimize the risk of overcrowding that can cause various problems, both physical and psychological. Keywords: Occupancy; Density; Population; Family Resilience.